Enhancing Sharia compliance: Evaluating supervisory roles in a rural Islamic bank in Yogyakarta, Indonesia - Rahmatika, Dzuriyatun; Andriansyah, Yuli; Qubbaja, Adnan (Journal of Islamic Economics Lariba, 2024)
Introduction Islamic Rural Banks (Bank Perekonomian Rakyat Syariah abbreviated BPRS in Bahasa Indonesia) play a vital role in promoting Islamic finance in Indonesia. Central to their operation is the Sharia Supervisory Board (Dewan Pengawas Syariah abbreviated DPS in Bahasa Indonesia), tasked with ensuring that all financial activities align with Islamic principles. Despite their importance, gaps in the implementation of Sharia compliance suggest limitations in Sharia Supervisory Board effectiveness, which may undermine the integrity of Islamic Rural Banks operations. Objectives This study investigates the effectiveness of the Sharia Supervisory Board in maintaining Sharia compliance within an Islamic Rural Bank in Yogyakarta, Indonesia. It aims to identify key challenges, such as regulatory clarity, institutional support, and the qualifications of the Sharia Supervisory Board members, and their impact on the Islamic Rural Bank’s governance and performance. Method The research employs a mixed-methods approach, combining qualitative and quantitative analyses. Data were collected through structured interviews with Sharia Supervisory Board members, Islamic Rural Bank executives, and regulatory bodies, alongside a review of regulatory documents and institutional records. The study uses thematic analysis and statistical tools to evaluate the factors influencing the Sharia Supervisory Board’s effectiveness. Results Findings reveal that the effectiveness of the Sharia Supervisory Board is significantly influenced by their qualifications, access to training, and institutional support. Regulatory ambiguities lead to inconsistent Sharia compliance practices across Islamic Rural Banks. Institutions with robust internal frameworks and better resource allocation exhibit higher levels of Sharia compliance and customer trust. Implications The study highlights the necessity for comprehensive training programs, more explicit regulatory guidelines, and more substantial institutional support to enhance the role of the Sharia Supervisory Board. These improvements are essential for maintaining the credibility of Islamic financial institutions and fostering customer confidence. Originality/Novelty This research contributes to the literature on Islamic finance governance by addressing systemic and practical challenges faced by the Sharia Supervisory Board in Islamic Rural Banks. It offers actionable recommendations for policymakers, regulators, and financial institutions to strengthen the governance and compliance mechanisms in Islamic banking.